2018
DOI: 10.21037/atm.2018.05.13
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Roux-en-Y duodenojejunostomy for annular pancreas in adults: case report and literature review

Abstract: Annular pancreas is in adults is a rare congenital anomaly which incidence varied from 0.005% to 0.015%. Although 33% of the cases are symptomatic, the symptoms are most commonly associated with gastric outlet obstruction. Here we presented an adult diagnosed with annular pancreas treated by laparoscopic Roux-en-Y side to side duodenojejunostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…11 Although duodenoduodenostomy is a procedure of choice in infancy, gastrojejunostomy or duodenojejunostomy have been considered in adult patients due to less mobility of the duodenum. 3,4,12 The minimally invasive surgery is generally performed due to less postoperative complications and a short hospital stay. Laparoscopic gastrojejunostomy is a useful treatment modality of the annular pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Although duodenoduodenostomy is a procedure of choice in infancy, gastrojejunostomy or duodenojejunostomy have been considered in adult patients due to less mobility of the duodenum. 3,4,12 The minimally invasive surgery is generally performed due to less postoperative complications and a short hospital stay. Laparoscopic gastrojejunostomy is a useful treatment modality of the annular pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that laparoscopic duodenoduodenostomy and laparoscopic gastrojejunostomy are successfully performed in pediatric and adult patients. [3][4][5]11 To our experience, we suggest that laparoscopic Roux-en-Y gastrojejunostomy is a good procedure option for annular pancreas in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a preponderance of cases of annular pancreas in the infant/newborn population. It is exceptionally rare in the adult population with incidences varying from 0.005% to 0.015%, and presentation is variable and can include duodenal obstruction, pancreatitis or symptoms of peptic ulcer disease [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%